MYC Mediates Large Oncosome-Induced Fibroblast Reprogramming in Prostate Cancer - Valentina R. Minciacchi; Cristiana Spinelli; Mariana Reis-Sobreiro; Lorenzo Cavallini; Sungyong You; Mandana Zandian; Xiaohong Li; Rajeev Mishra; Paola Chiarugi; Rosalyn M. Adam; Edwin M. Posadas; Giuseppe Viglietto; et al. (2017)
Abstract Communication between cancer cells and the tumor microenvironment results in the modulation of complex signaling networks that facilitate tumor progression. Here, we describe a new mechanism of intercellular communication originating from large oncosomes (LO), which are cancer cell–derived, atypically large (1–10 μm) extracellular vesicles (EV). We demonstrate that, in the context of prostate cancer, LO harbor sustained AKT1 kinase activity, nominating them as active signaling platforms. Active AKT1 was detected in circulating EV from the plasma of metastatic prostate cancer patients and was LO specific. LO internalization induced reprogramming of human normal prostate fibroblasts as reflected by high levels of α-SMA, IL6, and MMP9. In turn, LO-reprogrammed normal prostate fibroblasts stimulated endothelial tube formation in vitro and promoted tumor growth in mice. Activation of stromal MYC was critical for this reprogramming and for the sustained cellular responses elicited by LO, both in vitro and in vivo in an AKT1-dependent manner. Inhibition of LO internalization prevented activation of MYC and impaired the tumor-supporting properties of fibroblasts. Overall, our data show that prostate cancer–derived LO powerfully promote establishment of a tumor-supportive environment by inducing a novel reprogramming of the stroma. This mechanism offers potential alternative options for patient treatment. Cancer Res; 77(9); 2306–17. ©2017 AACR.